2019
DOI: 10.1016/j.agrformet.2019.107632
|View full text |Cite
|
Sign up to set email alerts
|

Alley-cropping system increases vegetation heterogeneity and moderates extreme microclimates in oil palm plantations

Abstract: Forest conversion to oil palm plantation is causing a major loss of biodiversity in Southeast Asia and other tropical regions. Oil palm plantations have less biodiversity because of their simplified vegetation, human disturbances, and extreme microclimate conditions. Alleycropping system incorporates a secondary crop in the alleys between the main crops. In some cases alley-cropping can result in a greater vegetation structural complexity, thus potentially providing agricultural and ecological benefits, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…From the observation at these smallholding and large scale plantations, differences of the vegetation structure created from different planting designs and management between both plantations, greatly influence light penetration underneath tree canopies, thus affecting the microclimate and soil characteristics. Similarly, Ashraf et al (2019) also highlighted that the alley-cropping system used in oil palm polyculture plantation improved the vegetation heterogeneity and microclimate regulation, however, it is also especially important to carefully selecting the crops when incorporating them with the oil palm trees as the selected crop characteristics and surrounding vegetation structural characteristics may influence the microclimate and soil conditions of an area. This emphasizes that polyculture agricultural systems used in smallholdings may serve as an alternative to sustainable agricultural practice and consequently contribute to overcoming global warming and biodiversity conservation challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the observation at these smallholding and large scale plantations, differences of the vegetation structure created from different planting designs and management between both plantations, greatly influence light penetration underneath tree canopies, thus affecting the microclimate and soil characteristics. Similarly, Ashraf et al (2019) also highlighted that the alley-cropping system used in oil palm polyculture plantation improved the vegetation heterogeneity and microclimate regulation, however, it is also especially important to carefully selecting the crops when incorporating them with the oil palm trees as the selected crop characteristics and surrounding vegetation structural characteristics may influence the microclimate and soil conditions of an area. This emphasizes that polyculture agricultural systems used in smallholdings may serve as an alternative to sustainable agricultural practice and consequently contribute to overcoming global warming and biodiversity conservation challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Age stand may also contribute to the differences between the findings in the smallholdings and large scale plantations. For example, Ashraf et al (2019) found that the monoculture oil palm plantation of different ages had different effects on microclimate conditions where a 15-year old oil palm showed lower solar radiation interception below canopy and higher relative humidity due to a more closed structure compared to a younger oil palm stand (7 year old).…”
Section: Discussionmentioning
confidence: 99%
“…Luas lahan perkebunan kelapa sawit di Indonesia pada tahun 2015 telah mencapai 11.6 juta ha (Kementan, 2016). Pemanfaatan lahan di bawah tegakan tanaman utama seperti di bawah perkebunan kelapa sawit terkendala oleh suhu udara yang rendah (Ashraf et al, 2019), ancaman kekeringan (Corley et al, 2018), tanah masam (Dhandapani et al, 2019), dan gangguan dari organisme pengganggu tanaman (Sopandie and Trikoesoemaningtyas, 2011). Lahan di bawah tegakan perkebunan kelapa sawit dikategorikan sebagai lahan marjinal karena faktor-faktor pembatas untuk pemanfaatannya.…”
Section: Pendahuluanunclassified
“…The influence of structural diversity of plants on microclimatic parameters has become increasingly clear [11]. In the intercropping system, the aboveground and belowground microclimates were changed through horizontal and vertical plant growth [12].…”
Section: Introductionmentioning
confidence: 99%